2019
DOI: 10.21276/ijcmr.2019.6.3.36
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Mass Index with Pulmonary Function Tests in North Indian Females

Abstract: Introduction:Obesity is becoming one of the serious public health problems of modern world with rapidly changing lifestyles involving consumption of high calorie foods with decreased physical activities. Spirometery is the initial screening tool for pulmonary diseases. The aim of this study was to evaluate the prevalence of deranged BMI, pulmonary function tests and correlation between BMI and pulmonary function test. Material and methods:This study was done on 300 female subjects in the age group of 18-25 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…24 Other studies by Kharodi et al, Ashraf et al, Biring et al, and Ahmed and Morgan also stated that obesity was associated with a significant decline of FEV 1 . 3,14,25,26 Contrary to our study, a study by Bhattacharjee et al showed a significant increase in FEV 1 with obesity. 21 In the present study, PEFR declined non-significantly (p >0.05) in group B when compared to group A as shown in Table 2.…”
Section: Materials a N D Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…24 Other studies by Kharodi et al, Ashraf et al, Biring et al, and Ahmed and Morgan also stated that obesity was associated with a significant decline of FEV 1 . 3,14,25,26 Contrary to our study, a study by Bhattacharjee et al showed a significant increase in FEV 1 with obesity. 21 In the present study, PEFR declined non-significantly (p >0.05) in group B when compared to group A as shown in Table 2.…”
Section: Materials a N D Methodscontrasting
confidence: 99%
“…A study by Kharodi et al revealed a significant decrease in pulmonary function tests in overweight and obese females who do not have any known obstructive airway disease. 3 The accumulation of fat may mechanically affect the expansion of the diaphragm, probably by encroaching into the chest by the chest wall or diaphragm 28 or by impending the descent of the diaphragm during forced inspiration. 18 Low FEV 1 and FVC values suggest restrictive lung pattern among obese persons.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were in line with the findings of Attaur-Rasool et al, (2012), who reported that FEV1% and FVC% were negatively correlated with BMI in both males (P < 0.001) and females adults (P < 0.022). Another study backed up the present findings that all pulmonary functions negatively correlate with BMI in the rural population (Kharodi et al, 2019).…”
Section: Discussionsupporting
confidence: 76%